1997
DOI: 10.1089/hum.1997.8.4-431
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Surfactant Inhibits Cationic Liposome-Mediated Gene Delivery to Respiratory Epithelial CellsIn Vitro

Abstract: Cationic lipid-mediated transfection of the alveolar epithelium in vivo will require exposure of plasmid DNA and cationic lipids to endogenous surfactant lipids and proteins in the alveolar space. Effects of pulmonary surfactant and of surfactant constituents on transfection in vitro of two respiratory epithelial cell lines (MLE-15 and H441) with a plasmid encoding the luciferase reporter gene were studied using two cationic lipid formulations: 1,2-dimyristyloxypropyl-3-dimethyl-hydroxyethyl ammonium bromide/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 24 publications
1
60
0
Order By: Relevance
“…8,22,23 Others have reported that Alveofact, a natural pulmonary surfactant, forms a barrier to cationic lipid-mediated gene transfer. [11][12][13] We examined whether this also held true for our lipoplexes.…”
Section: Does Alveofact Influence Gene Expression Zeta Potential Andmentioning
confidence: 91%
See 2 more Smart Citations
“…8,22,23 Others have reported that Alveofact, a natural pulmonary surfactant, forms a barrier to cationic lipid-mediated gene transfer. [11][12][13] We examined whether this also held true for our lipoplexes.…”
Section: Does Alveofact Influence Gene Expression Zeta Potential Andmentioning
confidence: 91%
“…Instead, at concentration ratios between 0.16 and 1.8 a significant increase was observed. Also, Duncan et al 11 have reported an increase in gene expression in the presence of Alveofact. They attributed this to binding of surfactant protein B and C, present in small amounts in Alveofact, to the surface of the cationic lipoplexes, which enhances their binding to epithelial cells.…”
Section: Does Alveofact Influence Gene Expression Zeta Potential Andmentioning
confidence: 96%
See 1 more Smart Citation
“…Viral vectors, the current favorites for intracellular DNA delivery, suffer from immunogenicity, nonspecificity, and inherent risks of complications such as the interference with the activity of tissue-specific promoters (8)(9)(10). Nonviral vectors such as cationic lipids͞liposomes (11) are nonspecific, demonstrate low efficiency compared with viruses, and can be inactivated by pulmonary surfactants (12) and serum proteins (13). Cytotoxic reactions such as pulmonary inflammation (14), antiproliferative activity in proteoglycan-deficient cells (15), production of reactive oxygen intermediates (16), and inhibition of NO and tumor necrosis factor-␣ production in activated macrophages (17) were reported after cationic lipid͞liposome treatments.…”
mentioning
confidence: 99%
“…To this end novel vectors, both viral and nonviral, are being extensively studied. 5,6 Further, it is clear that a number of potential biological extra-and intracellular barriers to gene transfer exist, [7][8][9][10][11] and ways to overcome these are being intensively investigated. While these improvements in gene transfer technology are awaited, we asked whether simple changes to existing clinical protocols might be able to increase expression levels.…”
mentioning
confidence: 99%